Correlation between junk food consumption and caffeinated beverages on the nutritional status among college on food technology student in Slamet Riyadi University, Indonesia : Hubungan pola konsumsi junk food dan minuman berkafein terhadap status gizi mahasiswa teknologi pangan di Universitas Slamet Riyadi, Indonesia - Aninda Putri Cantikawanti; Yannie Asrie Widanti; Nanik Suhartatik (Fakultas Sains dan Teknologi Unisri, 2025)
Nutritional problems during the growth phase of adolescent are mostly caused by consumption patterns. The most commonly used eating patterns during adolescent are foods that are high in calories, fat, sugar and salt. The habits of an unhealthy eating pattern can affect nutritional status. The foods most consumed by adolescent are often junk food and caffeinated beverages. All kinds of food and drinks are easily found around campuses surrounded by student. The purpose of this study was to determine the relationship between junk food consumption and caffeinated beverages to the nutritional status of students of the Faculty of Technology and Food Industry at Slamet Riyadi University, Surakarta. The respondents involved were students aged 18-24 years. Data was collected using a questionnaire and interview to the student. Data were analyzed using Chi-Square test. The results showed that factor affecting the nutritional status of student was mother’s education (p=0,000) and father’s education (p=0.000). Factors that do not affect nutritional status were energy intake (p=0.545), protein (p=0.085), fat (p=0.204) and carbohydrate (p=0.112), the amount of pocket money (p=0.310), the consumption level of junk food (p=0.671) and caffeinated drinks (p=0.535). The results showed that there was no significant relationship between the consumption patterns of junk food and caffeinated drinks on the nutritional status of students of the Faculty of Food Technology and Industry at Slamet Riyadi University, Surakarta. Permasalahan gizi yang terjadi saat pertumbuhan fase remaja lebih banyak disebabkan karena pola konsumsi. Pola makan yang sering diterapkan pada masa remaja adalah makanan tinggi kalori, lemak, gula, dan garam. Pola makan yang tidak sehat dapat mempengaruhi status gizi seseorang. Makanan yang paling banyak dikonsumsi oleh kalangan remaja masuk dalam kategori junk food dan juga minuman berkafein. Makanan dan minuman kategori ini mudah ditemukan di sekitar kampus yang dikelilingi mahasiswa. Tujuan pada penelitian ini ialah menentukan hubungan pola konsumsi junk food dan minuman berkafein terhadap status gizi mahasiswa Fakultas Teknologi dan Industri Pangan di Universitas Slamet Riyadi, Surakarta. Responden yang terlibat ialah mahasiswa berusia 18-24 tahun. Pengumpulan data menggunakan kuesioner dan wawancara kepada mahasiswa. Analisis data menggunakan uji Chi-Square. Hasil penelitian menunjukkan bahwa faktor yang mempengaruhi status gizi mahasiswa adalah pendidikan ibu (p=0.000) dan pendidikan ayah (p=0.000). faktor yang tidak mempengaruhi status gizi ialah asupan energi (p=0.545), protein (p=0.085), lemak (p=0.204) and karbohidrat (p=0.112), jumlah uang saku (p=0.310), tingkat konsumsi junk food (p=0.671) dan minuman berkafein (p=0.535). Hasil penelitian menunjukkan tidak terdapat hubungan signifikan antara pola konsumsi junk food dan minuman berkafein terhadap status gizi mahasiswa Fakultas Teknologi dan Industri Pangan Universitas Slamet Riyadi, Surakarta.